Collision risk assessment between UAS and landing aircraft in restricted airspace surrounding an airport using 3D Monte-Carlo simulation - Wang, John Chung-Hung (2020)
The availability of off the shelf, easy to control, unmanned aerial systems (UAS) on the market has led to an increase in report of UAS incursion into aerodrome. Such incursions would often result in lengthy airport shutdowns and cause disruption to air traffic operations throughout the region. Additionally, advancement in UAS flight control, motor efficiency, and battery life made the UAS more attractive to cargo operators for carrying parcels, both in urban area and near major port of call. While advancements have been made in the past decade in detection and avoidance of UAS traffics, the systems depend on either having fully cooperative traffic or sensor capability beyond what is currently available. This paper presents a 3D collision risk assessment model that was created to assess both the collision risk posed by an intruding non-cooperative UAS, as well as the safety risk associated with UAS operating within the 5km restricted airspace using predetermined route. Monte-Carlo simulations based on the 3D flight dynamics of the UAS are used to calculate the probability of collision at each time-step under the different scenarios.